How (Not) to Fix Problems that Matter : Assessing and Responding to Malawi's History of Institutional Reform - Bridges, Kate (World Bank, Washington, DC, 2017)
Malawi can be understood as a microcosm of institutional reform approaches in developing countries more broadly. A common feature of such approaches, whether implemented by government or donors, is reform initiatives that yield institutions that "look like" those found in higher-performing countries but rarely acquire the same underlying functionality. This paper presents a retrospective analysis of previous institutional reform projects in Malawi, as well as interviews with Malawi-based development practitioners. The paper finds a plethora of interventions that, merely by virtue of appearing to be in conformity with "best practices" elsewhere, are deemed to be successful yet fail to fix underlying problems, sometimes in contradiction to internal and public narratives of positive progress. This unhappy arrangement endures because a multitude of imperatives, incentives, and norms appear to keep governments and donors from more closely examining why such intense, earnest, and long-standing efforts at reform have, to date, yielded so few successes. This paper seeks to promote a shift in approach to institutional reform, offering some practical recommendations for reform-minded managers, project teams, and political leaders in which the focus is placed on crafting solutions to problems that Malawians themselves nominate, prioritize, and enact.